ANALISIS TINGKAT KEPUASAAN PENGGUNA PORTAL WEB PPID DENGAN METODE EUCS PADA KANWIL KEMENAG PROVINSI SUMATERA SELATAN - Suhartini Yulianti; Freddy Kurnia Wijaya (Jurnal Riset Sistem Informasi, 2026)
The PPID Web Portal of the Regional Office of the Ministry of Religious Affairs of South Sumatra serves as a primary platform for providing public information in a fast and transparent manner. To ensure that the portal truly meets the needs of its users, an evaluation of user satisfaction is required. This study aims to analyze user satisfaction with the portal using the End User Computing Satisfaction (EUCS) method, which assesses five key dimensions: content, accuracy, format, ease of use, and timeliness. The research employed a descriptive quantitative approach by distributing questionnaires to 104 respondents who had previously accessed the PPID Web Portal. All research instruments were confirmed to be valid and reliable based on the validity and reliability tests. Regression analysis shows that four variables accuracy, format, ease of use, and timeliness have a significant influence on user satisfaction. In contrast, the content variable does not show a significant effect, indicating that the information provided on the portal does not yet fully meet user needs or expectations. The simultaneous F-test demonstrates that all EUCS variables collectively have a significant impact on user satisfaction, with an Adjusted R² value of 0.839, meaning that most variations in user satisfaction can be explained by these five variables. Overall, the portal has provided adequate information services, particularly in terms of data accuracy, interface design, usability, and timeliness of updates. Nevertheless, improving the quality of content should be a priority to ensure a more comprehensive and user-aligned information service experience.